Advances in Environmental Law - Arjjumend, Hasrat (TGI Books/ The Grassroots Institute, 2024)
Advances in Environmental Law is a ground-breaking exploration of the ever-evolving field of environmental jurisprudence, providing a comprehensive examination of key themes such as Environmental Law, Climate Law, European Law, Globalization, Indigenous Peoples, Right to Clean Environment, Environmental Litigation, Clean Energy, Sustainable Development, and Environmental Policy. Authored by leading experts in the field, this book serves as a vital resource for legal professionals, policymakers, academics, and anyone passionate about the intersection of law and environmental sustainability. Foreworded by eminent and high stature legal scientist, Prof. Dr. Anatoly Getman, who is State honoured esteemed Rector of Ukraine's the only National Law University in the name of Yaroslav the Wise, this book begins by dissecting the foundations of Environmental Law, offering a detailed analysis of international and domestic legal frameworks that shape environmental governance. It delves into the intricate web of treaties, conventions, and agreements that guide nations in their commitment to preserving the planet's health. A significant focus is placed on Climate Law, exploring the legal mechanisms designed to address the urgent challenges of climate change. The book navigates through international climate agreements, domestic legislation, and the role of environmental courts in shaping policies aimed at mitigating and adapting to the impacts of a changing climate. In the context of European Law, the book investigates the specific legal frameworks within the European Union that govern environmental protection and sustainability. It explores landmark cases and legislative developments that have shaped the continent's approach to ecological conservation and climate action. Globalization emerges as a key theme, with the book scrutinizing the legal implications of interconnected economies on environmental practices. It addresses the challenges and opportunities presented by the globalized nature of environmental issues, emphasizing the need for transnational cooperation and legal instruments. Indigenous Peoples' rights and their role in environmental governance are explored in depth, recognizing the unique perspectives and contributions of indigenous communities in environmental conservation. The book critically examines legal frameworks that safeguard indigenous knowledge and territories. The Right to a Clean Environment is a fundamental principle underpinning the book's exploration. It discusses the evolution of this right and its implications for legal systems worldwide, emphasizing its role in shaping environmental policies and promoting justice. Environmental Litigation is scrutinized as a powerful tool for advocacy and accountability. The book analyses landmark environmental cases, shedding light on the role of the judiciary in influencing environmental policies and holding violators accountable. Clean Energy and Sustainable Development are discussed in the context of legal frameworks that promote the transition to environmentally friendly practices. The book examines the role of law in incentivizing clean energy initiatives and fostering sustainable development. Environmental Policy is a recurring theme throughout the book, with a focus on the development, implementation, and evaluation of policies aimed at addressing pressing environmental challenges.